Utilization of Instagram as a public relations publication media for the central statistics agency of Blora district - Yudhista, Arya; Mahendra P, Angga Intueri (Journal of Intelligent Decision Support System (IDSS), 2023)
This research is based on the increasingly widespread use of social media among the public and also government agencies. Instagram has become a social media that is increasingly used to disseminate various information by uploading various photos and videos to attract more audiences. In this case, BPS Blora Regency also participates in utilizing Instagram social media as a space to publish various information related to statistical data, member recruitment, and other interesting information. The management of Instagram social media to attract many audiences also requires the ability of Instagram admin in framing space with audiences in the media. This research will analyze the 4C elements described by Chris Heur regarding the use of social media which include Context, Communication, Collaboration, and Connection. In this study, researchers used a qualitative approach with descriptive qualitative research methods. The data collection techniques in this research are interviews and documentation. The conclusion in this research shows that the social media of BPS Blora Regency has described the 4C elements, but it is not optimal in terms of collaboration